Pemberontakan Petani Unra 1943 (Studi Kasus Mengenai Gerakan Sosial Di Sulawesi Selatan Pada Masa Pendudukan Jepang) - Kamaruddin, Syamsu A. (Makara Human Behavior Studies in Asia, 2012)
The research aims to describe the beckground, condition, and factors leading to the uprising of peasants in Unra during the era of Japanese occupation in South Sulawesi in the year 1943. In the analysis of the revolt of Unra peasants as a social movement, I examine the factors, conditions, and community structures that served as the bases of the uprising. Factors such as ideologies and leadership are also considered in order to know the extent to which they motivated and contributed to the event. In the same way, the study also focuses on the cultural and religious backgrounds within the historical context of the revolt, along with the social, economic, and political climates in Unra during the Japanese occupation. In order to reconstruct this historic movement, a qualitative research method is employed from a historical perspective. A historical method is used to analyze the process and developmental stages in a chronological fashion. Historical analysis was done using approaches from other disciplines such as sociology, anthropology, and political science in order to obtain a broader understanding of the revolt. The goal of this approach is to discover the processes of social change and other social indications that may have been involved such as social conflict, disorganization, and lack of integration among rural communities. Research results show that during the time of Japanese rule in Indonesia, particularly in the year 1943 in Unra, a rapid social change occurred and a wartime economic policy was forced upon the people. This then became the motivating factor behind the uprising of peasants as a social movement.